2017
DOI: 10.1007/s00705-017-3648-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and genomic characteristics of canine kobuvirus in southwest China

Abstract: To investigate canine kobuvirus (CaKoV) infection in southwest China, 107 fecal samples were collected from dogs with obvious diarrhea in Sichuan and Chongqing regions, China. CaKoV infection was detected in 54 diarrheic samples (50.46%) by RT-PCR targeting a partial fragment (504 bp) of the 3D gene. Comparison of these partial 3D gene sequences from 14 of these CaKoV-positive samples show 95.4%-99.0% nucleotide (nt) identity within this group, and nt identities ranging from 93.1% to 98.2% with previously repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 18 publications
6
12
0
Order By: Relevance
“…The CaKoV-positive rate observed in this study (16.13%) was similar to those reported previously in diarrheic dogs in northeast China (17.91%) [17], South Korea (19.0%) [25], and Thailand (17.59%) [18] and lower than those reported in southwest China (50.46%) [22] and Japan (37.2%) [15]. The CaKoV-positive rates in diarrheic dogs observed in the United States, Italy, and Brazil were lower (3%, 4.4%, and 5.7%, respectively) than that observed in our study [4,12,19].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The CaKoV-positive rate observed in this study (16.13%) was similar to those reported previously in diarrheic dogs in northeast China (17.91%) [17], South Korea (19.0%) [25], and Thailand (17.59%) [18] and lower than those reported in southwest China (50.46%) [22] and Japan (37.2%) [15]. The CaKoV-positive rates in diarrheic dogs observed in the United States, Italy, and Brazil were lower (3%, 4.4%, and 5.7%, respectively) than that observed in our study [4,12,19].…”
Section: Discussionsupporting
confidence: 90%
“…These data indicate that CaKoVpositive rates may differ between different countries or regions. Some studies have found CaKoV not only in dogs with gastroenteritis but also in healthy animals [15,18,22,25]. In this study, CaKoV was detected in 20% (4/20) of dogs without diarrhea symptoms.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…The first described canine circovirus case had severe necrotising vasculitis and granulomatous disease, as well as haemorrhagic gastroenteritis. Li et al (2013a) examined histological samples from dogs with similar pathological findings and were able to identify a further Kong et al (2016) 4.7% a 0% Li et al (2017) 50.5% NP Korea Oem et al (2014) 19% 13.2% Choi et al (2014 50.6% NP Japan Soma et al (2016) 37.2% 48.0%…”
Section: Epidemiology and Pathogenesismentioning
confidence: 99%
“…The structural proteins form the capsid, which is associated with the adsorption and entry of virus particles into cells. Based on the sequence of the VP1 gene, virus strains can be divided into two groups [12]. The non-structural proteins and intermediates are involved in RNA replication, polyprotein cleavage, and virion assembly [9].…”
Section: Introductionmentioning
confidence: 99%